Destruction of rocks by the non-explosive depleting compounds during mining - Sakhno, S.; Kobyliansky, i В.; Sakhno, I. (Розробка родовищ, 2016)
Purpose. Justification of the possibility of non-explosive coherent rocks destruction while carrying out stratal underground
mine workings on the basis of the set of dependencies describing changes in physical and mechanical properties
of the non-explosive depleting compounds (NDC) during hydration process in the blast-hole charges in relation
to crack growth in the adjacent area.
Methods. By conducting experiments on the unequal component triaxial compression unit, we obtained the dependence
of changes in the physical and mechanical properties of the NDC on the hydration time and the relationships
between the physical and mechanical properties. The required distance between the blast-holes with NDC was established
analytically for non-explosive destruction by quasi-static pressure of the compound expansion.
Findings. The study allowed to obtain empirical dependences of medium stress change, coefficient of transverse
strain, strain modulus of the NDC for compound expansion in time. The dependence of the strain modulus of the
NDC on medium stress has been established. The research resulted in the analytical dependence of the length of the
crack progressing from the blast-hole walls into the massif depth while implementing non-explosive technologies of
destruction on the compound expansion pressure, its elastic constants as well as physical and mechanical characteristics
of the medium under destruction.
Originality. Medium stresses caused by the NDC expansion grow in time similarly to the growth of the stress
tensor components, the dependence of the strain modulus on average stresses being satisfactorily described by an
exponential dependence.
Practical implications. The results of experimental and theoretical studies, taking into account sufficient accuracy
for practical applications, can be used to determine parameters of the quasi-static rocks breaking by non-explosive
compound during stratal mining. Цель. Обоснование возможности невзрывного разрушения прочных горных пород при проведении пластовых подземных горных выработок, исходя из установленных зависимостей изменения физико-механических
свойств невзрывчатых разрушающих смесей (НРС) в процессе гидратации в шпуровых зарядах на рост трещин
в околошпуровой области.
Методика. Экспериментальным путем на установке неравнокомпонентного трехосного сжатия установлена
зависимость изменения физико-механических свойств НРС от времени гидратации, а также связь между физико-механическими свойствами. Аналитически установлено необходимое расстояние между шпурами с НРС при
реализации невзрывного разрушения квазистатическим давлением расширения смеси.
Результаты. Получены эмпирические зависимости изменения среднего напряжения, коэффициента поперечной деформации, модуля деформации НРС при расширении смеси во времени. Установлена зависимость
модуля деформации НРС от среднего напряжения. Получена аналитическая зависимость длины трещины развивающейся от стенок шпура вглубь массива при реализации технологии невзрывного разрушения от давления
расширения смеси, ее упругих констант и физико-механических свойств разрушаемой среды.
Научная новизна. Средние напряжения, вызванные расширением НРС, растут во времени по характеру
аналогично росту компонентов тензора напряжений, при этом зависимость модуля деформации от средних
напряжений удовлетворительно описывается экспоненциальной зависимостью.
Практическая значимость. Полученные результаты экспериментальных и теоретических исследований, с
достаточной для практического применения точностью, могут использоваться для определения параметров
квазистатического разрушения горных пород невзрывчатыми смесями при проведении пластовых горных выработок. Это существенно повысит безопасность работ, расширит область невзрывного проведения на породы с
высокой прочностью. Мета. Обґрунтування можливості невибухового руйнування міцних гірських порід при проведенні пластових підземних гірничих виробок, виходячи зі встановлених залежностей зміни фізико-механічних властивостей
невибухових руйнуючих сумішей (НРС) у процесі гідратації в шпурових зарядах на ріст тріщин в навколошпуровой області.
Методика. Експериментальним шляхом на установці нерівнокомпонентного тривісного стиску встановлена
залежність зміни фізико-механічних властивостей НРС від часу гідратації, а також зв’язок між фізико-механічними властивостями. Аналітично встановлено необхідну відстань між шпурами з НРС при реалізації
невибухового руйнування квазистатичним тиском розширення суміші.
Результати. Отримано емпіричні залежності зміни середньої напруги, коефіцієнта поперечної деформації,
модуля деформації НРС при розширенні суміші у часі. Встановлено залежність модуля деформації НРС від
середньої напруги. Отримано аналітичну залежність довжини тріщини, що розвивається від стінок шпуру вглиб
масиву при реалізації технології невибухового руйнування від тиску розширення суміші, її пружних констант і
фізико-механічних властивостей середовища, що руйнується.
Наукова новизна. Середні напруження, викликані розширенням НРС, ростуть у часі за характером аналогічно росту компонентів тензора напружень, при цьому залежність модуля деформації від середніх напружень
задовільно описується експоненціальною залежністю.
Практична значимість. Отримані результати експериментальних і теоретичних досліджень, з достатньою
для практичного застосування точністю, можуть використовуватися для визначення параметрів квазістатичного
руйнування гірських порід невибуховими сумішами при проведенні пластових гірничих виробок. Це істотно
підвищить безпеку робіт, розширить область невибухового проведення на породи з високою міцністю.